433 Determining the haematological morbidity associated with cytoreductive surgery. (13th November 2020) - Corry, E; Bartels, H; Mulhall, J; Grundy, J; Mulsow, J; Brennan, D
Abstract : Introduction: Cytoreductive surgery (CRS) is a complex procedure performed in the setting of epithelial ovarian cancer (EOC), pseudomyxoma peritonei (PMP) and colorectal metastases (CRCm). Due to the complexity of the surgery with significant fluid volume exchange calculating estimated blood loss (EBL) is challenging. To determine the hematological morbidity associated with CRS we reviewed the EBL and transfusion rates in a National Peritoneal Cancer Centre. Method: The surgical oncology anonymized database provided data on demographics, surgical oncological intervention, timing, EBL, laboratory measurements, and transfusion requirements. The EBL recorded from the operative notes calculated in the operating room by the gravimetric method (suction volume and swab weights). Results: A total of 120 patients who underwent CRS± HIPEC, with a median age of 57 were included. The median EBL for the entire cohort (n=120) was 981 ml (range 50–6500). The median EBL for metastatic colorectal CRS (n=38) was 830 ml (range 50–3800 ml), for ovarian cancer (n= 51) was 900 ml (range 150–4600 ml) and for PMP (n=31) was 1300 (range 100–6500). The average number of red cells (RCC) transfused for the entire cohort was 1.14 (SEM 0.147), and was similar for ovarian cancer (1.28 (SEM 0.251) and PMP (1.26 (SEM 0.314)) but was significantly lower in the colorectal metastases group (0.87(SEM 0.189). Conclusion: CRS for EOC, PMP, or CRCm is associated with significant hematological morbidity, which should be taken into account for pre-operative optimization. The variation in EBL reflects the heterogeneous nature of these complex procedures, with more extensive surgery often warranted in PMP and EOC.